24=-16t-(-t-3)

Simple and best practice solution for 24=-16t-(-t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=-16t-(-t-3) equation:


Simplifying
24 = -16t + -1(-1t + -3)

Reorder the terms:
24 = -16t + -1(-3 + -1t)
24 = -16t + (-3 * -1 + -1t * -1)
24 = -16t + (3 + 1t)

Reorder the terms:
24 = 3 + -16t + 1t

Combine like terms: -16t + 1t = -15t
24 = 3 + -15t

Solving
24 = 3 + -15t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '15t' to each side of the equation.
24 + 15t = 3 + -15t + 15t

Combine like terms: -15t + 15t = 0
24 + 15t = 3 + 0
24 + 15t = 3

Add '-24' to each side of the equation.
24 + -24 + 15t = 3 + -24

Combine like terms: 24 + -24 = 0
0 + 15t = 3 + -24
15t = 3 + -24

Combine like terms: 3 + -24 = -21
15t = -21

Divide each side by '15'.
t = -1.4

Simplifying
t = -1.4

See similar equations:

| 4/5d=-12 | | 2/3x-1=0 | | -4-3=-6x+9 | | 1/5s=-4 | | 5(3x-5)-4(x+2)-17x= | | (x-8)(x-5)=x | | -24=7x+x | | 5x+8=3x+35 | | 3x+16.5=0 | | 17=5p-4+6 | | 7x-1+7(x+1)=6x+1 | | 17=-4-4k-3k | | -12.2=6.6t+2(-6.3t-3.6) | | -18=6-6m | | 39=-2x+7 | | 12.6=-49k+4(8.5k-0.6) | | 10a-9=-79 | | 3(7r-6)-9r=12r+1 | | 5x-7.5=0 | | 66=-5x+10 | | 7x-9=4(3x-1) | | X^2-18=90 | | 10-4(3x+2y)= | | -5x-20-7x=-68 | | -3(5y+6)-3(y-8)= | | -14=-8+2w | | 3(3r+3)-2(r-1)= | | 7b=4(b+30) | | 2ln(2x)=6 | | -2(3y-1)-2(y-6)= | | (x^2-2x+4)(x^2+3x-11)=0 | | x-13=19+3x |

Equations solver categories